Long-term control of parathyroid hormone and calcium-phosphate metabolism after parathyroidectomy in children with chronic kidney disease - Schäfer, Betti; Schlosser, Katja; Wühl, Elke; Schall, Petra; Klaus, Günter; Schaefer, Franz; Schmitt, Claus P. (Nephrology, dialysis, transplantation, 2010)
Background. Hyperparathyroidism (HPT) is an essential contributor to bone disease and cardiovascular calcifications in children with chronic kidney disease (CKD). Pharmacological and dietary interventions are of limited efficacy; calcimimetics are not yet recommended in children. Parathyroidectomy (PTX) is ultimately performed if HPT becomes refractory to conservative measures; the long-term results and the impact of subsequent kidney transplantation (NTX), however, have not yet been evaluated.Methods. We analyzed the postsurgical course of 18 paediatric CKD patients with refractory HPT who underwent PTX and autotransplantation of tissue fragments. PTX was successful in all but one patient with an ectopic fifth gland; median follow-up time was 8.3 (range 2.8-19) years.Results. Parathyroid hormone (PTH) dropped within 1 year after PTX from 1030 ± 108 to 98 ± 18 pg/ml, Ca*P from 59.5 ± 3 to 49 ± 2 mg2/dl2. Oral calcium supply transiently increased from 18.7 ± 4.2 to 24.1 ± 4.8 mg/kg/day within the first 6 months (all P < 0.05). Haemoglobin increased from 10.7 ± 0.4 to 11.5 ± 0.3 g/dl (P < 0.01), despite similar erythropoietin dose and ferritin levels. In patients on long-term dialysis, Ca*P increased again after 18 months; three patients required a second PTX after 3.8, 12 and 12.3 years. Twelve patients underwent NTX 1.8 (0.3-3.8) years after PTX, which decreased mean PTH and Ca*P into the target range throughout the entire post-NTX observation period. Postoperative complications included one transient recurrent nerve palsy, one hypocalcaemic seizure and a case of haemopericardium. At present, no patient has clinical signs of bone disease.Conclusions. PTX accomplishes long-term control of HPT and calcium-phosphate metabolism in children with CKD and following PTX and may thus mitigate uraemic bone and cardiovascular disease. This has to be taken into account if alternative long-term therapy with calcimimetics (with as yet unknown effects on longitudinal growth and pubertal development) is considered.
Gesehen am 09.08.2023